In vivo measurement of volumetric strain in the human brain induced by arterial pulsation and harmonic waves - Hirsch, Sebastian; Klatt, Dieter; Freimann, Florian; Scheel, Michael; Braun, Juergen; Sack, Ingolf (Magnetic Resonance in Medicine, 2013)
Motion-sensitive phase contrast magnetic resonance imaging and magnetic resonance elastography are applied for the measurement of volumetric strain and tissue compressibility in human brain. Volumetric strain calculated by the divergence operator using a biphasic effective-medium model is related to dilatation and compression of fluid spaces during harmonic stimulation of the head or during intracranial passage of the arterial pulse wave. In six volunteers, phase contrast magnetic resonance imaging showed that the central cerebrum expands at arterial pulse wave to strain values of (2.8 ± 1.9)·10-4. The evolution of volumetric strain agrees well with the magnitude of the harmonic divergence measured in eight volunteers by magnetic resonance elastography using external activation of 25 Hz vibration frequency. Intracranial volumetric strain was proven sensitive to venous pressure altered by abdominal muscle contraction. In eight volunteers, an increase in volumetric strain due to abdominal muscle contraction of approximately 45% was observed (P = 0.0001). The corresponding compression modulus in the range of 9.5-13.5 kPa demonstrated that the compressibility of brain tissue at 25 Hz stimulation is much higher than that of water. This pilot study provides the background for compression-sensitive magnetic resonance imaging with or without external head stimulation. Volumetric strain may be sensitive to fluid flow abnormalities or pressure imbalances between vasculature and parenchyma as seen in hydrocephalus. Copyright © 2012 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2022-08-03
Keywords: brain tissue; cerebral pulsation; compression waves; flow field; harmonic motion field; magnetic resonance elastography; poroelastography; porosity; shear waves; venous pressure